Genetic diversity and structure in two epiphytic orchids from the montane forests of southern Ecuador: The role of overcollection on Masdevallia rosea in comparison with the widespread Pleurothallis lilijae - Riofrío, María (2023)
Ecuador has a high diversity of orchids, but little is known about levels of genetic diversity for the great majority of species. Understanding how orchids might adapt to changes is crucial as deforestation and fragmentation of forest ecosystems threaten the survival of many epiphytic orchids that depend on other species, such as fungi and their host trees, for germination, growth, and establishment. Overcollection and the illegal trade are also major concerns for the survival of wild populations of orchids. Despite increasing awareness, effective interventions are often limited by a lack of data concerning the impacts that overexploitation might have. To fill this gap, we tested the effects of overcollection in the genetic diversity and structure of Masdevallia rosea, a narrow distributed epiphytic orchid historically collected in Ecuador, in comparison with the widely distributed Pleurothallis lilijae. Genotyping based on AFLPs showed reduced levels of diversity in wild populations but most especially in the overcollected, M. rosea. Overall, genetic admixture was high in P. lilijae segregating populations by altitude levels while fewer genetic groups were found in M. rosea. Genetic differentiation was low in both species. A spatial genetic structure was found in P. lilijae depending on altitude levels, while no spatial genetic structure was found in M. rosea. These results suggest different scenarios for the two species: while gene flow over long distance is possible in P. lilijae, the same seems to be unlikely in M. rosea possibly due to the low levels of individuals in the known populations. In situ and ex situ conservation strategies should be applied to protect the genetic pool in these epiphytic orchid species, and to promote the connectivity between wild populations. Adopting measures to reduce overexploitation and to understand the impacts of harvesting in wild populations are necessary to strengthen the legal trade of orchids.